Evaluation of the strength and the ductility of shear connectors in (steel-concrete) composite beams. « Evaluation de la résistance et la ductilité des connecteurs dans les poutres mixtes (acier-béton) - MAGHAGHI, Bilal (UNIVERSITE DE M’SILA, 2022)
The overall behavior of steel-concrete composite beams largely depends on the connection used to transfer shear forces at the interface between steel and concrete members. Nevertheless, the majority of failure occurs in this sensitive area. Therefore, it is necessary to improve the connection performance in the steel-concrete composite beams. However, the most common shear connectors used worldwide are headed stud connectors and channel shear connectors due to many advantages. In the first part of the present thesis, five new channel shear connector shapes, and a new stud connector shape, are proposed and studied experimentally. A total of twenty push-out tests using a new setup, and three pull-out tests, were carried out under monotonic loading to identify the shapes that give the best performance. The failure modes, the effects of new channel and stud connectors shapes on the load-slip behavior, the concrete slabs, the bending deformation, and other parameters were studied. The study showed that the modification of both channel and stud connector shapes is a promising way and positively influences the concrete-connector relationship and also the bending deformation capacity of these shear connectors. As a result, the concrete cracking decreased, the ductility increased in the range of 15-31%, and the ultimate strength improved slightly from 0 to 5.1% for channel connectors. As for the stud connectors, their ductility increased to reach around 22%, but a slight decrease was observed in its ultimate strength (6%). As a second part, a three-dimensional (3D) finite element model was developed to simulate the push-out specimen of the shear connectors that carried the best performance in the first step. The proposed model was validated by comparing the numerical results with those of experimental tests. This simulation provided the full behavioral details of connectors and the effect of some other parameters. In addition, a 3D finite element model of a steel-concrete composite beam with four bending points was also developed. Finally, a parametric study was carried out to evaluate the influence of various parameters. As a result, the connection degrees and the concrete strength significantly affect the overall behavior of the steel-concrete composite beams. Meanwhile, the connectors ‘steel grade does not affect their performance.
Keywords: Steel-concrete composite beams, connectors, new setup of push-out test, FEA